Development of Creative Skills of Students in Solution of Some Problems of Vectoral, Mixed and Double Multiplications of Vectors (Eurasian Research Bulletin, 2022)
This article considers some aspects of the development of creative activities of students in solving some problems related to vectorial and mixed multiplication, and gives concrete examples of the use of each studied method in the teaching of analytical geometry.